Model Project Based Learning (PjBL) Berbantuan Media Game Biosentence Challenge untuk Meningkatkan Hasil Belajar Murid Kelas VIII di SMP Negeri 26 Makassar - Arfan Sudirman; Rifda Nurhikmawati Arif (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to improve the learning outcomes of eighth-grade students at SMP Negeri 26 Makassar in the subject of biotechnology through the implementation of the Project-Based Learning (PjBL) model aided by the Biosentence Challenge game. This study is a Classroom Action Research (CAR) conducted in three cycles, each consisting of one session, covering the stages of planning, implementation, observation, and reflection. The Biosentence Challenge game is a word-building game designed to form sentences relevant to biotechnology concepts. A practical activity involving the production of sweet potato tapai was integrated as a real-world project into the learning process. Data collection instruments included a pretest, formative tests at the end of each cycle, and a posttest following the third cycle. The research results showed a significant improvement in learning outcomes, marked by an increase in the average formative test score from 72.4 in Cycle I to 83.8 in Cycle II, and 98.3 in Cycle III. A comparison of the pretest (77.7) and posttest (93.35) scores revealed an increase of 15.65 points. The class N-gain analysis was 0.67 (moderate category) with 11 students in the high category, and the analysis by indicator showed the highest improvement in C3 (Applying) with an N-gain of 0.70 and C4 (Analyzing) with an N-gain of 0.71. The implementation of the game-assisted PjBL model proved capable of optimally improving students’ motivation, active engagement, and conceptual understanding of biotechnology material.